Road Performance Evaluation on the Kalitanjung Road Section in Cirebon City - Guruh Menda, Rafi; Robby Mauluddin, Robby; Rojali, Mohamad (Ridwan Institute, 2025)
Road performance needs to be taken into consideration because side obstacles, namely human activities, affect the performance of the road. The problem in this study is traffic congestion on the road, and the objective of this study is to evaluate the performanceof the road. The analysis method uses the 2023 PKJI guidelines. The data collection in this study consists of primary and secondary data. Primary data was obtained through observations, including: data surveys of vehicle volume (traffic counters), and observations of external obstacles. Meanwhile, secondary data was obtained through Google Earth. The research results show that the performance of the Kalitanjung road section has a service level of 0.8, derived from the analysis of the degree of saturation (DJ) as a reference for road service level or LOS (Level of Service) PKJI 2023, categorized as LOS “D,” meaning it is approaching unstable with decreasing speed. The survey results over 6 days showed a peak hour vehicle count of 4,583 vehicles/hour or a traffic flow rate (Q) of 2,104.65 vehicles per hour. Additional supporting analyses include: free-flow speed (VB) value of 34.776 km/hour, capacity (C) value of 2,646 vehicles per hour, travel time (WT) of 0.016 hours or 57.6 seconds per 400-meter road segment length. The analysis also indicates that the road is currently operating at 70% of its capacity, with a free-flow speed of 34.776 km/hour.